Influence of global postural reeducation method on respiratory muscle strength and parkinsonian quality of life - Rocha, Larissa Salgado de Oliveira; Mineshita, Larissa Natsumi Hosoda; Sobral, Luciane Lobato; Magno, Lizandra Dias; Santos, Marcio Clementino de Souza; Rocha, Rodrigo Santiago Barbosa (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Degenerative diseases such as Parkinson’s disease can lead to postural changes and muscular strength, this generates greater impact on the individual, on his functional capacity, respiratory system, mobility and, quality of life (QOL). Objective: The aim of this study was to verify the influence of the Global Posture Reeducation (GPR) method on respiratory muscle strength and QOL in patients with Parkinson’s disease. Methods: Twenty volunteers, the average of age is 48.8 ± 6.22 years, they are diagnosed with Parkinson’s disease at level 2 to 3 by the Hoehn & Yahr Scale. They were submitted to the protocol of treatment with the GPR method in the postures of Frog in the ground and ballerina, performed regularly twice a week lasting 60 minutes each session, for 6 weeks, totaling 12 sessions, evaluated by PDQ-39 quality of life questionnaire and by inspiratory pressure measurements and Maximum expiratory value. Results: In the quantitative analysis of inspiratory and expiratory muscle pressure, there was an increase in post-treatment for maximal inspiratory pressure (MIP) (p <0.05) when compared to pre-treatment, as well as when compared with predicted values MIP and maximum expiratory pressure (MEP) presented higher values (p <0.05). In terms of QoL domains: mobility (p = 0.0009), daily life activity (p = 0.0006), emotional well-being (p = 0.001), cognition (p = 0.01) and physical discomfort were statistically significant in post-treatment. Conclusion: The use of GPR in Parkinson’s disease has shown to be effective in the treatment of respiratory muscle strength and QoL.